Cognitive Judgment Bias Interacts with Risk Based Decision Making and Sensitivity to Dopaminergic Challenge in Male Rats - Drozd, Robert; Cieslak, Przemyslaw E.; Rychlik, Michal; Rodriguez Parkitna, Jan; Rygula, Rafal (Frontiers in Behavioral Neuroscience, 2016)
Although cognitive theory has implicated judgement bias in various psychopathologies, its role in decision making under risk remains relatively unexplored. In the present study we assessed the effects of cognitive judgment bias on risky choices in rats. First, we trained and tested the animals on the rat version of the probability-discounting task. During discrete trials, the rats chose between two levers; a press on the ‘small/certain’ lever always resulted in the delivery of one reward pellet, whereas a press on the ‘large/risky’ lever resulted in the delivery of four pellets. However, the probability of receiving a reward from the ‘large/risky’ lever gradually decreased over the four trial blocks. Subsequently, the rats were re-trained and evaluated on a series of ambiguous-cue interpretation tests, which permitted their classification according to the display of ‘optimistic’ or ‘pessimistic’ traits. Because dopamine has been implicated in both: risky choices and optimism, in the last experiment, we compared the reactivity of the dopaminergic system in the ‘optimistic’ and ‘pessimistic’ animals using the apomorphine (2mg/kg s.c.) sensitivity test. We demonstrated that as risk increased, the proportion of risky lever choices decreased significantly slower in ‘optimists’ compared with ‘pessimists’ and that these differences between the two groups of rats were associated with different levels of dopaminergic system reactivity. Our findings suggest that cognitive judgement bias, risky decision-making and dopamine are linked, and they provide a foundation for further investigation of the behavioural traits and cognitive processes that influence risky choices in animal models.